If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(8 + -2) + -1x(3x + -7) = -6(4x + -6x) + x Combine like terms: 8 + -2 = 6 5(6) + -1x(3x + -7) = -6(4x + -6x) + x Multiply 5 * 6 30 + -1x(3x + -7) = -6(4x + -6x) + x Reorder the terms: 30 + -1x(-7 + 3x) = -6(4x + -6x) + x 30 + (-7 * -1x + 3x * -1x) = -6(4x + -6x) + x 30 + (7x + -3x2) = -6(4x + -6x) + x Combine like terms: 4x + -6x = -2x 30 + 7x + -3x2 = -6(-2x) + x Remove parenthesis around (-2x) 30 + 7x + -3x2 = -6 * -2x + x Multiply -6 * -2 30 + 7x + -3x2 = 12x + x Combine like terms: 12x + x = 13x 30 + 7x + -3x2 = 13x Solving 30 + 7x + -3x2 = 13x Solving for variable 'x'. Reorder the terms: 30 + 7x + -13x + -3x2 = 13x + -13x Combine like terms: 7x + -13x = -6x 30 + -6x + -3x2 = 13x + -13x Combine like terms: 13x + -13x = 0 30 + -6x + -3x2 = 0 Factor out the Greatest Common Factor (GCF), '3'. 3(10 + -2x + -1x2) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(10 + -2x + -1x2)' equal to zero and attempt to solve: Simplifying 10 + -2x + -1x2 = 0 Solving 10 + -2x + -1x2 = 0 Begin completing the square. Divide all terms by -1 the coefficient of the squared term: Divide each side by '-1'. -10 + 2x + x2 = 0 Move the constant term to the right: Add '10' to each side of the equation. -10 + 2x + 10 + x2 = 0 + 10 Reorder the terms: -10 + 10 + 2x + x2 = 0 + 10 Combine like terms: -10 + 10 = 0 0 + 2x + x2 = 0 + 10 2x + x2 = 0 + 10 Combine like terms: 0 + 10 = 10 2x + x2 = 10 The x term is 2x. Take half its coefficient (1). Square it (1) and add it to both sides. Add '1' to each side of the equation. 2x + 1 + x2 = 10 + 1 Reorder the terms: 1 + 2x + x2 = 10 + 1 Combine like terms: 10 + 1 = 11 1 + 2x + x2 = 11 Factor a perfect square on the left side: (x + 1)(x + 1) = 11 Calculate the square root of the right side: 3.31662479 Break this problem into two subproblems by setting (x + 1) equal to 3.31662479 and -3.31662479.Subproblem 1
x + 1 = 3.31662479 Simplifying x + 1 = 3.31662479 Reorder the terms: 1 + x = 3.31662479 Solving 1 + x = 3.31662479 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 3.31662479 + -1 Combine like terms: 1 + -1 = 0 0 + x = 3.31662479 + -1 x = 3.31662479 + -1 Combine like terms: 3.31662479 + -1 = 2.31662479 x = 2.31662479 Simplifying x = 2.31662479Subproblem 2
x + 1 = -3.31662479 Simplifying x + 1 = -3.31662479 Reorder the terms: 1 + x = -3.31662479 Solving 1 + x = -3.31662479 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = -3.31662479 + -1 Combine like terms: 1 + -1 = 0 0 + x = -3.31662479 + -1 x = -3.31662479 + -1 Combine like terms: -3.31662479 + -1 = -4.31662479 x = -4.31662479 Simplifying x = -4.31662479Solution
The solution to the problem is based on the solutions from the subproblems. x = {2.31662479, -4.31662479}Solution
x = {2.31662479, -4.31662479}
| 4v+8=26v-2v | | 15/m+62=23 | | x^2+6x-107=0 | | (5x+20)+3x=180 | | ln(x+4)+lnx-2=0 | | 5x-3[18-2(x-1)]=10 | | (x-4)(x-3)=20 | | 47n=6n^2 | | 5x+40=5(6x+8) | | X(x-26)=-160 | | -12+n=25 | | 4=6a-2wT-14 | | b/3=5 | | 9x+5=2(5x-4) | | 3x+8=-79-9x | | 24+2=-6(8m-4) | | 3-z/8=4 | | 3y-10=47+10/3 | | x^2-0.6=-0.6x | | 2(x+8)=21+2x | | -2(3y-7)=7 | | 9+8.9*3= | | -6(1-4)-3(3-7)= | | 5x-12=9x+8 | | 9z=13-31 | | -8(1+5b)=21 | | 13k-6=9k+2 | | 7.9=d | | 58=27-t | | 9x-7y=-12 | | -8=k/-4 | | 9y-11-5y=26 |